2001
DOI: 10.1016/s0735-1097(01)01591-1
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of interleukin-1β in the acute phase of myocardial infarction promotes the progression of left ventricular remodeling

Abstract: Anti-IL-1beta treatment suppressed pro-collagen gene expression and delayed wound healing mechanisms-properties that are likely to lead to progression of LV remodeling. In the acute phase of MI, IL-1beta appears to play a protective role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 27 publications
3
94
1
1
Order By: Relevance
“…Earlier studies showed deleterious consequences (including a worsening of ventricular remodeling) following inhibition of fibrotic healing or the inflammatory response after infarction by means of corticosteroids. 29,30 Recent research on genetically modified mice has also demonstrated the adverse consequences of impaired fibrotic healing after MI leading to aggravated ventricular rupture and remodeling, 31,32 although the suppression of excessive matrix deposition is believed to be beneficial in the context of stem cell based therapies. Our findings showed that fibrotic healing post-infarction can be therapeutically remodeled by relaxin leading to a reduced density of fibrotic tissue across infarcted, non-infarcted, and border zones.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed deleterious consequences (including a worsening of ventricular remodeling) following inhibition of fibrotic healing or the inflammatory response after infarction by means of corticosteroids. 29,30 Recent research on genetically modified mice has also demonstrated the adverse consequences of impaired fibrotic healing after MI leading to aggravated ventricular rupture and remodeling, 31,32 although the suppression of excessive matrix deposition is believed to be beneficial in the context of stem cell based therapies. Our findings showed that fibrotic healing post-infarction can be therapeutically remodeled by relaxin leading to a reduced density of fibrotic tissue across infarcted, non-infarcted, and border zones.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac transfection with human IL-1Ra significantly decreased infarct size, reduced apoptosis, and attenuated the inflammatory response in rat hearts undergoing ischemia/ reperfusion protocols [160], suggesting an injurious role for IL-1 in the ischemic myocardium. In contrast, another investigation suggested a protective role for IL-1 demonstrating that IL-1β neutralization in the acute phase of myocardial infarction resulted in increased occurrence of cardiac rupture and enhanced adverse remodeling [161]. Because IL-1 signals exclusively through the IL-1 receptor type I (IL-1RI) we have recently examined the effects of disrupted IL-1 signaling on infarct healing and cardiac remodeling using IL-1RI −/− mice [162].…”
Section: The Il-1 Familymentioning
confidence: 99%
“…Animal experiments showed that a neutralizing antibody against IL-1β and Anakinra, a recombinant IL-1 receptor antagonist (IL-1RA), exerted beneficial effects on acute MI. 28,29) Furthermore, inflammatory responses can occur more aggressively in myocardial I/R compared with permanent MI. 1) These fi ndings allow us to assume that inflammasomes may play a substantial role in the pathophysiology of myocardial I/R injury.…”
Section: Nlrp3 Inflammasome and Myocardial Infarction (Mi)mentioning
confidence: 99%
“…Second, because inflammation also plays a critical role in the process of cardiac healing after MI, inhibition of infl ammation may infl uence cardiac rupture and aneurysm formation. An initial study by Hwang, et al 28) suggested that neutralization of IL-1β reduced collagen accumulation in the heart after experimental MI and increased the occurrence of cardiac rupture. However, impaired cardiac healing and increased rupture after MI were not observed in the studies using genetic deletion of IL-1 receptor or pharmacological blockades (Anakinra or IL-1 trap [rilonacept]).…”
Section: Nlrp3 Inflammasome and Myocardial Infarction (Mi)mentioning
confidence: 99%